Cyberbullying di Media Sosial - Ni Luh Ayu Mondrisa Dwipayana; Setiyono Setiyono; Hatarto Pakpahan (University of Merdeka Malang, 2020)
The development of community needs in information technology plays a very important role, both in positive and negative sides. One of the most disturbing and developing cyber crimes today is crimes related to a person’s freedom of privacy, namely cyber bullying. The issues raised were the application of positive laws regarding the crime of cyberbullying as a cybercrime crime and the cause of bullying that occurred on social media. The research method used is the normative research method, due to the absence of norms for regulatingcyber bullying in Law Number 11 of 2008 concerning Electronic Information and Transactions as amended by Law Number 19 of 2016 concerning Electronic Information and Transactions.. Cyberbullying is a new type of crime when viewed from the media used, namely electronic media, the easier it is to make social media a place to commit cyberbullying crimes from several reasons that are intended to fulfill aggressive attitudes and personal feelings that dominate the perpetrator, then this should be the concern of all law enforcers wherecyberbullying is rampant on social media. Therefore, for the cyberbullying phenomenon, the application of positive law on the crime of cybebullying has been explained based on article 27 paragraph (3) of Law Number 19 of 2016, amendments to Law number 11 of 2008 concerning Electronic Information and Transactions, and has a relationship between articles 310 and 311 of the Criminal Code, and the Constitutional Court Decisions Number 50 / PUU-VI / 2008 concerning complaint offenses referring to the phenomenon of cyberbullying